2020
DOI: 10.12737/stp-64202004
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Magnetospheric Responses to Interaction With Diamagnetic Structures of Slow Solar Wind

Abstract: We propose a possible classification of the responses of the magnetosphere to the interaction with diamagnetic structures (DS), which form the basis of the slow solar wind. The main determinants of the classification are the value and orientation of the vertical component Bz of the interplanetary magnetic field (IMF) and the solar wind density N. We have identified three types of magnetospheric responses. Type 1 has two subtypes whose main difference is the presence or absence of auroras on the day side of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Our results and the results of studies of the DSmagnetosphere interaction reported in [Parkhomov et al, 2015[Parkhomov et al, , 2020[Parkhomov et al, , 2021 can be explained by the model [McPherron et al, 1986] presented in Figure 9, a. The model was built on the basis of a large statistics of observations of global isolated substorms, which were triggered by a sharp change in the long-term (~2 hrs) northward orientation of IMF Bz to the southward.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Our results and the results of studies of the DSmagnetosphere interaction reported in [Parkhomov et al, 2015[Parkhomov et al, , 2020[Parkhomov et al, , 2021 can be explained by the model [McPherron et al, 1986] presented in Figure 9, a. The model was built on the basis of a large statistics of observations of global isolated substorms, which were triggered by a sharp change in the long-term (~2 hrs) northward orientation of IMF Bz to the southward.…”
Section: Resultssupporting
confidence: 67%
“…At 09:40 UT there was a density jump to N≈13 cm -3 ; at 10:13 UT the density increased to ~21 cm -3 , and at 10:40 UT it reached its maximum value of 33 cm -3 . Specifically, the IMF modulus varies in antiphase with the density (r=-0.74), which, as noted above, is an indication of the diamagnetic structure [Parkhomov et al, 2018].…”
Section: Identification Of Ds In Earth's Orbit On December 22 2015 An...mentioning
confidence: 72%
See 2 more Smart Citations
“…Sperveslage et al, 2000;Winterhalter et al, 1994) or mirror mode structures created when the plasma is marginally mirror unstable (Karlsson et al, 2021). Other theories are that the magnetic holes are the result of non-linear interaction of Alfvén waves with the solar wind plasma (Buti et al, 2001;Tsurutani, Dasgupta, et al, 2002;Tsurutani, Galvan, et al, 2002), emerging coherent structures in solar wind turbulence (Perrone et al, 2016;Roytershteyn et al, 2015), or diamagnetic structures formed in the solar corona (Parkhomov et al, 2019).…”
Section: Introductionmentioning
confidence: 99%